Contemporary trends in the development of public procurement law in South Africa - Quinot, Geo (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
This paper explores emerging contemporary trends in the development of South Africa’s public procurement law. Using a doctrinal legal analysis, it identifies two main trends in such development post-democratization, one structural and one substantive. It argues that these two trends pose particular challenges to the public procurement system. At the structural level, the paper shows that while law has played a key role in the development of South Africa’s public procurement system right from the outset, it constituted a light touch regulatory regime prior to the constitutional transition in 1994. The changes that the new constitutional dispensation brought about necessitated an adjustment in the regulation of public procurement as well. The development of public procurement law to effect such adjustment has, however, created a fragmented, uncoordinated and overly burdensome regulatory regime. At the substantive level, the paper argues that law has not managed to effectively create a framework for the use of public procurement for social policy purposes with specific reference to the pursuit of equality. Based on these findings, the paper argues that legal reform is urgently needed in order to avoid law undermining the public procurement function in South Africa.